2014
DOI: 10.1186/s13012-014-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ contributions to tailored implementation programs: an observational study of group interview methods

Abstract: BackgroundTailored strategies to implement evidence-based practice can be generated in several ways. In this study, we explored the usefulness of group interviews for generating these strategies, focused on improving healthcare for patients with chronic diseases.MethodsParticipants included at least four categories of stakeholders (researchers, quality officers, health professionals, and external stakeholders) in five countries. Interviews comprised brainstorming followed by a structured interview and focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…However, little is known about how best to identify important barriers and how to select interventions to address identified barriers [ 12 , 13 ]. The TICD project conducted some ground-breaking research comparing different methods for identifying determinants of practice [ 16 ] and for linking interventions to those determinants [ 14 ]. However, our trial was limited to comparisons of tailored strategies to no intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about how best to identify important barriers and how to select interventions to address identified barriers [ 12 , 13 ]. The TICD project conducted some ground-breaking research comparing different methods for identifying determinants of practice [ 16 ] and for linking interventions to those determinants [ 14 ]. However, our trial was limited to comparisons of tailored strategies to no intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the five countries in the TICD project selected between eight and 30 determinants for discussion in focus groups. The methods, setting, study sample and group interviews are presented in detail elsewhere [ 19 , 20 ]. Here we briefly describe how we conducted our study in Norway.…”
Section: Methodsmentioning
confidence: 99%
“…In a joint analysis of the studies to tailor interventions in the TICD project, Huntink and colleagues [ 20 ] found no relationship between the total number of suggested interventions and the number of unique suggestions (interventions only suggested by one group).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The international project tailored intervention for chronic diseases (TICD) focused on the development and evaluation of a tailored implementation programme [8]. We followed subsequent steps starting with identifying barriers and enablers (so-called determinants) of current practice of CVRM care in general practice in the Netherlands and strategies to address these [911]. Next, we developed a tailored intervention programme, comprising of the prioritised strategies.…”
Section: Introductionmentioning
confidence: 99%